Analysis Of Creatinine Levels In Failed Patients Chronic Kidney Pre And Post Hemodialization At Santa Elisabeth Hospital Medan Year 2022 - Paska R Situmorang; Paka Brema Kaban; David Sumanto Napitupulu (Sean Institute, 2022)
Chronic renal failure (CKD) is a clinical syndrome due to a persistent decline in kidney function due to nephron damage. Efforts reduce serum creatinine levels are of course by improving the function of the kidneys, namely by hemodialysis. This study aims to analyze the results of blood creatinine levels in patients with chronic renal failure pre and post hemodialysis at Santa Elisabeth Hospital Medan 2022. This study uses a descriptive cross-sectional approach with population in this study are 178 people and a sample of 64 people. Data collection is carried out using an analyzer. The results showed an increase in pre-hemodialysis creatinine levels as many as 33 samples (51.6%). and results of post hemodialysis decreased by 29 samples (45.3%). The results of the average pre and post hemodialysis blood creatinine levels show that the pre hemodialysis blood creatinine average level was 8.5398 mg/dl. The post hemodialysis average blood creatinine level is 5.4333 mg/dl. It can be concluded that there is a change in the pre-hemodialysis average blood creatinine level. and post hemodialysis is 4 mg/dl. From the results of measurements of blood creatinine levels of the study sample, it was found that most of the patients undergoing hemodialysis were abnormal